A rare case of refractory active antibody mediated rejection who had recurrence of immunoglobulin a nephropathy in the form of crescentic glomerulonephritis - Kandari, Sharon; Biswal, Anshuman; Kant, Ravi; Puri, Rohit; Ahlawat, Parul; Cheriyan, Anil; Kaur, Sandeep; Gangdev, Abhay (International Journal of Research in Medical Sciences, 2025)
Immunoglobulin A nephropathy is one of the most common recurrent glomerulonephritis after kidney transplantation. Recurrence rate is around 30% at 10 years after transplant. Rarely, rapid deterioration of renal function may occur suggestive of presence of crescents. Presence of donor specific antibodies can predict poor transplant outcomes. Compliance to immunosuppressive medications will prevent development of donor specific antibodies and prolong allograft survival. Authors hereby report a case of refractory active antibody mediated rejection who developed recurrent Immunoglobulin A nephropathy 3 years after renal transplantation.